Solve the simultaneous equations 2x - y = 13, x - 2y = 11

  1. In order to solve simultaneous equations, you need to make either terms of x (i.e. '2x') or terms of y (i.e. 'y') in equation (1) and equation (2) equal. To do this, multiply either (1) or (2) as shown below.

(1) 2x - y = 13     (x2)           =       (1) 4x - 2y = 26

(2) x - 2y = 11                               (2) x - 2y = 11 

  1. Cancel out the alike terms (in this case, '2y') and follow the equation through. Important: remember the rules about adding and subtracting +s and -s. 

   (1) 4x - 2y = 26

(2) x - 2y = 11                        < (A minus and a minus equal a plus! In other words -2y - -2y = -2y + 2y = 0)

= 4x - x = 26 - 11

3x = 15

x = 5

  1. Substitute your new value for x into one of the original equations and follow through.

x - 2y = 11  becomes  5 - 2y = 11

5 - 11 = 2y

  • 6 = 2y

-3 = y

x = 5 and y = -3

Answered by Graciella M. Maths tutor

16346 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Solve: 2x^2 + x = x^2 - 4(x+1)


A pizza has a radius of 12cm. Calculate the area of the pizza in cm² , giving your answer as a multiple of π.


The mean of 5 numbers is 42. The 5 numbers are 45,29,63,42 and X. Find the value of X.


Make s the subject of the equation: 4st + 8 = 5r


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences